Thermal interface material
A thermal interface material with a polyolefin, thermally conductive fillers, and a phase change material addresses the issue of pump-out during power cycling, ensuring stable thermal conductivity in electronic devices.
Patent Information
- Application Number
- JP2023535897
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-24
- Publication Date
- 2024-12-19
- Estimated Expiration
- 2040-12-24
AI Technical Summary
Thermal interface materials (TIMs) used in electronic devices tend to pump out and separate during power cycling, especially in bare die designs, leading to increased bulk and interfacial thermal resistance, which is unacceptable in high-end applications.
A thermal interface material comprising a polyolefin with at least two hydroxy groups, thermally conductive fillers, a phase change material with a melting point of 25 to 150°C, and a coupling agent, with specific mass content ratios, to prevent pump-out during temperature changes.
The material softens with temperature increases during power cycling without pumping out, maintaining effective thermal conductivity and reducing thermal impedance.
Smart Images

Figure 0007603165000001 
Figure 0007603165000002 
Figure 0007603165000003
Abstract
Description
[Technical field]
[0001] The present invention relates to thermal interface materials. [Background technology]
[0002] A thermal interface material (TIM) is a thermally conductive material useful for heat transfer between two components in an electronic device. For example, TIMs are typically used to transfer heat from a heat-generating electronic component, such as a central processing unit (CPU) or a graphic processing unit (GPU), to a heat spreader, such as a heat sink. In recent years, heat-generating electronic components have been using increasing power and have increasing functionality requiring higher heat dissipation. There is also a trend towards using bare die designs for applications such as GPUs and AI chips. Thus, the thermal impedance (TI) of a TIM is typically less than 0.1°C·cm 2 It is desirable to have a value of less than 1 / W.
[0003] TIMs for heat transfer in electronic devices are well known in the art. For example, Patent Document 1 describes a thermally conductive material that includes (a) 100 parts by weight of wax, (b) 10 to 1,000 parts by weight of a liquid polymer such as polyisobutylene, (c) 10 to 2,000 parts by weight of a thermally conductive filler, and (d) 0 to 1,000 parts by weight of a softener.
[0004] Patent Document 2 describes a thermal interface material comprising at least one polymer, at least one thermally conductive filler, and at least one phase change material, wherein the at least one phase change material comprises a wax having a penetration value of at least 50 determined at 25° C. in accordance with ASTM D1321.
[0005] Patent Document 3 describes a thermal interface material including at least one phase change material, at least one polymer matrix material, at least one first thermally conductive filler having a first particle size, and at least one second thermally conductive filler having a second particle size.
[0006] Patent Document 4 describes a thermally conductive composition that includes a thermally conductive filler, a phase change material having a melting point of 35 to 120°C, a nonionic surfactant, and a binder composed of nonvolatile components, in which the content of the phase change material is 10 parts by mass or more, the content of the nonionic surfactant is 60 parts by mass or more, and the content of the nonvolatile components is 30 parts by mass or less, relative to 100 parts by mass of the binder.
[0007] However, TIMs typically pump out and separate from two components in an electronic device during power cycling, especially when the two components have different thermal expansion coefficients. Bare die designs can result in a large amount of pump out because the TIM is applied directly between the integrated circuit (IC) and the metal heat sink. The pump out leads to an increase in bulk thermal resistance and an increase in interface resistance. In high-end applications, such changes in both bulk and interface resistance are unacceptable due to the resulting dramatic changes in performance. The TIM should also be stable against pump out due to power cycling in bare die designs such as GPUs or AI chips. The TIM should exhibit minimal pump out of less than 5% after at least 5000 power cycles.
[0008] Prior art documents Patent Literature Patent Document 1: International Publication No. 2003 / 004580(A1) Patent Document 2: International Publication No. 2015 / 120773(A1) Patent Document 3: International Publication No. 2016 / 086410(A1) Patent Document 4: International Publication No. 2016 / 185936(A1) Summary of the Invention
[0009] technical issues It is an object of the present invention to provide a thermal interface material that softens but does not pump out as its temperature increases in an electronic device during power cycling.
[0010] Solutions to the problem The thermal interface material of the present invention comprises: (A) a polyolefin having at least two hydroxy groups per molecule; (B) at least one thermally conductive filler; (C) a phase change material having a melting point of 25 to 150°C; (D) a coupling agent, The content of component (B) is at least 80 mass %, the content of component (C) is 0.01 to 1 mass %, and the content of component (D) is 0.1 to 1 mass %, each based on the total mass of the thermal interface material.
[0011] In various embodiments, component (A) has the following general formula: [ka] In the formula, each R 1 , R 2 , and R 3 are independently a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 12 carbon atoms, and all R 1 ~R 3 at least two of the above are hydroxy groups, "m" is a positive number, and "n" is 0 or a positive number, with the proviso that "m+n" is a positive number that satisfies the number average molecular weight of 2,000 to 100,000 as measured by gel permeation chromatography.
[0012] In various embodiments, component (B) is at least one thermally conductive filler selected from alumina, aluminum, zinc oxide, boron nitride, aluminum nitride, or aluminum oxide trihydrate.
[0013] In various embodiments, component (C) is 12 -C 25 Alcohol, C. 12 -C 25 acid, C 12 -C 25 At least one phase change material selected from esters, waxes, or combinations thereof.
[0014] In various embodiments, component (D) is at least one coupling agent selected from a silicon-based coupling agent, a titanium-based coupling agent, or an aluminum-based coupling agent.
[0015] In various embodiments, component (D) has the following general formula: [ka] In the formula, each R 4 are independently an alkyl group having 6 to 15 carbon atoms, and each R 5 are independently an alkyl group having 1 to 5 carbon atoms or an alkenyl group having 2 to 6 carbon atoms, and each R 6 are independently an alkyl group having 1 to 4 carbon atoms, "a" is an integer from 1 to 3, and "b" is an integer from 0 to 2, with the proviso that "a+b" is an integer from 1 to 3.
[0016] In various embodiments, the thermal interface material further comprises (E) an antioxidant.
[0017] In various embodiments, the thermal interface material further comprises (F) a filler-polymer interaction enhancer.
[0018] In various embodiments, component (F) is at least one filler-polymer interaction promoter selected from liquid polybutadiene, silane-grafted polyolefin, or bis(trialkoxysilylalkyl)amine.
[0019] In various embodiments, the thermal interface material further comprises (G) a solvent.
[0020] Effect of the Invention The thermal interface material of the present invention becomes softer as its temperature increases in an electronic device during power cycling, but does not pump out.
[0021] definition The term "comprising" is used broadly herein to mean and encompass the concepts of "including" or "including," "consist(ing) essentially of," and "consist(ing) of." The use of "for example," "eg," "such as," and "including" to list examples does not limit the examples listed. Thus, "for example" or "such as" means "for example, but not limited to" or "such as, but not limited to," and encompasses other similar or equivalent examples. As used herein, the term "about" serves to reasonably encompass or account for slight variations in numerical values as determined by instrumental analysis or as a result of handling samples. Such slight variations may be on the order of ±0-25%, ±0-10%, ±0-5%, or ±0-2.5% of the numerical value. Furthermore, the term "about" applies to both numerical values when relating to a range of values. Furthermore, the term "about" may apply to numerical values even if not expressly stated.
[0022] The term "thermal impedance" or "TI" is used herein to mean the effectiveness of a TIM. The thermal impedance of a TIM between substrates is given by the following formula: [ka] It is calculated by where Θ is the thermal impedance of the TIM, d is the bond line thickness (BLT), κ is the thermal conductivity of the TIM, and R contact is the sum of the contact resistances of the TIM and the adjacent substrate. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] The thermal interface material of the present invention will now be described in detail.
[0024] Component (A) is a matrix material for dispersing component (B), and is a polyolefin having at least two hydroxyl groups in one molecule. Exemplary polyolefins of component (A) include polyethylene, polypropylene, polyisobutylene, ethylene-propylene copolymer, ethylene-isobutylene copolymer, ethylene-butylene-styrene copolymer; and hydrogenated polymers such as hydrogenated polyalkyldiene polyol (including hydrogenated polybutadiene polyol, hydrogenated polypropadiene polyol, and hydrogenated polypentadiene monool), and hydrogenated polyalkyldiene diol (including hydrogenated polybutadiene diol, hydrogenated polypropadiene diol, and hydrogenated polypentadiene diol).
[0025] In particular, component (A) preferably has the following general formula: [ka]
[0026] In the above formula, each R 1 , R 2 and R 3 are each independently a hydrogen atom, a hydroxyl group, or an alkyl group having 1 to 12 carbon atoms, provided that all R 1 ~R 3provided that at least two of the following are hydroxy groups: Examples of alkyl groups in the above formula include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, neopentyl, hexyl, cyclohexyl, heptyl, octyl, nonyl, decyl, undecyl, and dodecyl groups;
[0027] In the above formula, "m" is a positive number and "n" is 0 or a number, and m+n is a positive number that satisfies a number average molecular weight of 2,000 to 100,000, preferably 3,000 to 100,000, measured by gel permeation chromatography.
[0028] The state of component (A) at 25° C. is not limited, but is preferably a solid. Component (A) preferably has a melt viscosity, for example, a melt viscosity at 45° C. of 1 to 100 Pa·s. In this specification, the viscosity can be measured in accordance with JIS K7117-1: Plastics-Liquid, Emulsions or Dispersions Resins-Measuring Method of Apparent Viscosity by Brookfield Rotational Viscometer, or ISO 2555: Plastics Resins in the Liquid State or as Emulsions or Dispersions Determination of Apparent Viscosity by the Brookfield Teste Method.
[0029] An exemplary commercially available polyolefin is NISSO-PB GI-3000 available from Nippon Soda Co., Ltd.
[0030] Component (B) is at least one thermally conductive filler that can be any of those useful in TIMs. For example, component (B) can be any one or any combination of two or more thermally conductive fillers selected from metals, alloys, nonmetals, metal oxides, or ceramics. Exemplary metals include, but are not limited to, aluminum, copper, silver, zinc, nickel, tin, indium, and lead. Exemplary nonmetals include, but are not limited to, carbon, graphite, carbon nanotubes, carbon fibers, graphene, and silicon nitride. Exemplary metal oxides and ceramics include, but are not limited to, alumina, aluminum nitride, boron nitride, zinc oxide, and tin oxide. Desirably, component (B) is any one or any combination of two or more selected from the group consisting of alumina, aluminum, zinc oxide, boron nitride, aluminum nitride, and aluminum oxide trihydrate. Even more preferably, component (B) is any one or any combination or two or more fillers selected from spherical aluminum particles having an average particle size of 5-15 μm, spherical aluminum particles having an average particle size of 1-3 μm, and zinc oxide particles having an average particle size of 0.1-0.5 μm. The average particle size of the filler particles is determined as the median particle size (D50) using a laser diffraction particle size analyzer (CILAS 920 particle size distribution analyzer or Beckman Coulter LS 13 320 SW) according to the operating software.
[0031] The amount of component (B), based on the total weight of the thermal interface material, is at least 80%, preferably 85% or more, or even 90% or more, and at the same time is typically 95% or less, 94% or less, or even 93% or less, by weight.
[0032] Component (C) is a phase change material that undergoes a reversible solid-liquid phase change at the operating temperature of the electronic device. Component (C) has a melting point of 25-150°C, preferably 25-100°C, 25-80°C, or 25-70°C. When component (C) is cooled below its melting point, it solidifies without significant change in volume, thereby maintaining intimate contact between the heat-generating electronic component and the heat spreader. In this specification, the melting point (°C) may be measured by a Differential Scanning Calorimeter (DSC) in accordance with ASTM D3418.
[0033] Exemplary phase change materials for component (C) include C 12 -C 25 Alcohol, C. 12 -C 25 acid, C 12 -C 25 esters, waxes, and combinations thereof. 12 -C 25 The acids and alcohols include myristyl alcohol, 1,2-tetradecanediol, cetyl alcohol, stearyl alcohol, 1-eicosanol, pentacosanol, myristic acid, and stearic acid. Preferred waxes include microcrystalline wax, paraffin wax, and other wax-like waxes such as octadecane, nonadecane, eicosane, heneicosane, docosane, tricosane, triacontane, and hexatriacontane. 18 -C 40 Examples of such olefins include olefins.
[0034] The amount of component (C) is in the range of 0.01 to 1% by mass of the thermal interface material. However, based on the mass of the thermal interface material, it is desirably 0.05% by mass or more, 0.15% by mass or more, or even 0.2% by mass or more, and at the same time, typically 2.0% by mass or less, 1.5% by mass or less, 1.0% by mass or less, or even 0.5% by mass or less. This is because when the content of component (C) is equal to or more than the lower limit of the above range, the material has good handleability, whereas when the content of component (D) is equal to or less than the upper limit of the above range, the physical properties of the material are good.
[0035] Component (D) is a coupling agent that is useful for aiding the dispersion of component (B) in component (A). Component (D) is not particularly limited, but is preferably a silicon-based coupling agent, a titanium-based coupling agent, or an aluminum-based coupling agent.
[0036] The silicon based coupling agent preferably has the following general formula: [ka]
[0037] In the formula, R 4 are independently an alkyl group having 6 to 15 carbon atoms. Exemplary alkyl groups include a hexyl group, a heptyl group, an octyl group, a nonyl group, a decyl group, an undecyl group, and a dodecyl group.
[0038] In the formula, R 5 are independently an alkyl group having 1 to 5 carbon atoms or an alkenyl group having 2 to 6 carbon atoms. Exemplary alkyl groups include methyl, ethyl, propyl, isopropyl, butyl, isobutyl, tert-butyl, pentyl, and neopentyl groups. Exemplary alkenyl groups include vinyl, allyl, butenyl, pentenyl, and hexenyl groups.
[0039] In the formula, R 6are independently an alkyl group having 1 to 4 carbon atoms. Exemplary alkyl groups include a methyl group, an ethyl group, a propyl group, an isopropyl group, a butyl group, an isobutyl group, and a tert-butyl group.
[0040] In the formula, "a" is an integer from 1 to 3 and "b" is an integer from 0 to 2, with the proviso that "a+b" is an integer from 1 to 3, or "a" is 1 and "b" is an integer of 0 or 1, or "a" is 1 and "b" is 0.
[0041] Exemplary silicon-based coupling agents of component (D) include hexyltrimethoxysilane, heptyltrimethoxysilane, octyltriethoxysilane, decyltrimethoxysilane, dodecyltrimethoxysilane, dodecylmethyldimethoxysilane, dodecyltriethoxysilane, tetradecyltrimethoxysilane, octadecyltrimethoxysilane, octadecylmethyldimethoxysilane, octadecyltriethoxysilane, nonadecyltrimethoxysilane, and any combination of at least two thereof.
[0042] Exemplary titanium-based coupling agents of component (D) include isopropyl triisostearoyl titanate, isopropyl tris(dioctyl pyrophosphate) titanate, isopropyl tri(N-amidoethyl, aminoethyl) titanate, tetraoctyl bis(ditridecyl phosphate) titanate, tetra(2,2-diallyloxymethyl-1-butyl) bis(ditridecyl) phosphate titanate, bis(dioctyl pyrophosphate) oxyacetate titanate, and the like. titanate, bis(dioctylpyrophosphate)ethylene titanate, isopropyl trioctanoyl titanate, isopropyl dimethacryl isostearoyl titanate, isopropyl tridodecylbenzenesulfonyl titanate, isopropyl isostearoyl diacryl titanate, isopropyl tri(dioctylphosphate) titanate, isopropyl tricumylphenyl titanate, and tetraisopropyl bis(dioctylphosphite) titanate.
[0043] Exemplary aluminum-based coupling agents for component (D) include alkyl acetoacetate aluminum diisopropylates.
[0044] The amount of component (D) is in the range of 0.1 to 1% by mass of the thermal interface material. However, based on the mass of the thermal interface material, it is desirably 0.2% by mass or more, 0.3% by mass or more, or even 0.5% by mass or more, and at the same time, typically 3.0% by mass or less, 2.5% by mass or less, 2.0% by mass or less, or even 1.0% by mass or less. This is because when the content of component (D) is equal to or more than the lower limit of the above range, the dispersion of component (B) in the thermal interface material is good, whereas when the content of component (D) is equal to or less than the upper limit of the above range, the stability of the thermal interface material is good.
[0045] The thermal interface material may further comprise (E) an antioxidant. Exemplary antioxidants of component (E) include hindered phenols such as tetrakis[methylene(3,5-di-tert-butyl-4-hydroxyhydro-cinnamate)]methane; bis[(beta-(3,5-di-tert-butyl-4-hydroxybenzyl)methylcarboxyethyl)]-sulfide, 4,4'-thiobis(2-methyl-6-tert-butylphenol), 4,4'-thiobis(2-tert-butyl-5-methylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), and thiodiethylenebis(3,5-di-tert-butyl-4-hydroxy)-hydrocinnamate; tris(2,4-di-tert-butyl)- phosphites and phosphonites such as di-tert-butylphenyl)phosphite and di-tert-butylphenyl-phosphonite; thio compounds such as dilauryl thiodipropionate, dimyristyl thiodipropionate, and distearyl thiodipropionate; various siloxanes; polymeric 2,2,4-trimethyl-1,2-dihydroquinoline, n,n'-bis(1,4-dimethylpentyl-p-phenylenediamine), alkylated diphenylamines, 4,4'-bis(alpha,alpha-dimethylbenzyl)diphenylamine, diphenyl-p-phenylenediamine, mixed diaryl-p-phenylenediamines, and other hindered amine antidegradants or stabilizers.
[0046] The amount of component (E) is not limited, but is desirably 0.01% by weight or more, 0.05% by weight or more, or even 0.1% by weight or more, and at the same time is typically 1.0% by weight or less, 0.5% by weight or less, or even 0.2% by weight or less, based on the weight of the thermal interface material. This is because when the content of component (E) is equal to or greater than the lower limit of the above range, the stability of component (A) in the thermal interface material is good, whereas when the content of component (E) is equal to or less than the upper limit of the above range, the mechanical properties of the thermal interface material are good.
[0047] The material may further comprise (F) a filler-polymer interaction promoter. Component (F) is preferably at least one filler-polymer interaction promoter selected from liquid polybutadiene, silane-grafted polyolefin, silane-functionalized polyolefin obtained by reaction of maleated polyolefin, or bis(trialkoxysilylalkyl)amine. Exemplary liquid polybutadienes of component (F) include butadiene homopolymer, butadiene-styrene copolymer, and maleated polybutadiene. An exemplary commercially available liquid polybutadiene is Ricon® 130MA8 available from TOTAL Cray Valley.
[0048] The amount of component (F) is not limited, but is desirably 0.1% by weight or more, 0.5% by weight or more, or even 1.0% by weight or more, and at the same time is typically 3.0% by weight or less, 2.5% by weight or less, or even 2.0% by weight or less, based on the weight of the thermal interface material. This is because when the content of component (F) is equal to or greater than the lower limit of the above range, the stability of component (A) in the thermal interface material is good, whereas when the content of component (F) is equal to or less than the upper limit of the above range, the mechanical properties of the thermal interface material are good.
[0049] The material may further comprise (G) a solvent. Exemplary solvents of component (G) include aliphatic hydrocarbon solvents such as toluene, xylene, p-xylene, m-xylene, mesitylene, solvent naphtha H, solvent naphtha A, Isopar H, and other paraffin oils and isoparaffinic fluids; alkanes such as pentane, hexane, isohexane, heptane, nonane, octane, dodecane, 2-methylbutane, hexadecane, tridecane, pentadecane, cyclopentane, 2,2,4-trimethylpentane; and siloxane oligomers. An exemplary commercially available siloxane oligomer is DOWSIL OS-20 available from Dow Silicones Corporation.
[0050] The amount of component (G) is not limited, but is desirably 0.1% by weight or more, 0.5% by weight or more, 1.0% by weight or more, 1.5% by weight or more, or even 2.0% by weight or more, based on the weight of the thermal interface material, and at the same time, is typically 5.0% by weight or less, 3.0% by weight or less, or even 2.5% by weight or less. This is because when the content of component (G) is equal to or greater than the lower limit of the above range, the stability of component (A) in the material is good, whereas when the content of component (G) is equal to or less than the upper limit of the above range, the mechanical properties of the material are good.
[0051] The thermal interface material may further include additional components such as one or more additives, which may include, but are not limited to, antistatic agents, color enhancers, dyes, lubricants, fillers such as TiO2 or CaCO3, opacifiers, nucleating agents, pigments, processing aids, UV stabilizers, antiblocking agents, slip agents, tackifiers, flame retardants, antimicrobial agents, odor reducing agents, antifungal agents, and combinations thereof.
[0052] The thermal interface material can be prepared by mixing all of the components at ambient temperature. Any of the mixing techniques and equipment described in the prior art can be used for this purpose. The specific equipment used will be determined by the viscosity of the components and the final composition. Cooling the components during mixing may be desirable to avoid premature curing.
[0053] The thermal interface materials can be applied as a film that is die cut to the appropriate shape and applied directly onto the IC or heat sink prior to assembly, or conversely, the thermal interface materials can be printed onto the components as a thermal grease or compound for stencil or screen printing. EXAMPLES
[0054] The thermal interface material of the present invention will be described in detail below using examples and comparative examples. However, the present invention is not limited to the description of the examples listed below.
[0055] <Thermal Impedance (TI) and Bond Line Thickness (BLT) Test> Thermal impedance (TI) and bond line thickness (BLT) are evaluated by LW-9389 TIM Thermal Resistance and Conductivity Measurement Apparatus manufactured by LonGwin according to ASTM D-5470 standard. The pressure applied on the thermal interface material is 40 PSI. The test time is 15 minutes for one sample. The temperature is 80°C.
[0056] <Thermal testing vehicle (TTV) test> The following computer components are used in the tests: CPU: AMD Ryzen 7 2700X8-core, Motherboard: ASUS TUF X470-PLUS GAMING, Memory: KINSTON DDR4 2666 8GB, Graphics Card: ASUS Radeon RX Vega 64 8 GB Overlocked 2048-Bit HBM2 PCI Express 3.0 HDCP Ready Video Card, Solid State Drive: Intel SSD 760P Series (256GB, M.2 80mm PCle 3.0x4, 3D2, TLC, Monitor: Del U2417H, Keyboard: Dell, Mouse: Dell, PC case: Antec P8 ATX, ·Power supply: Antec NEO650W, KVM:MT-viki HK04.
[0057] TTV Programming: A GPU power cycle test was used to stress the GPU and push it to its absolute limits, reflecting the reliability of the Thermal Interface Material (TIM) applied on the chipset, especially to monitor for pump-out issues. This test was constructed with the goal of causing a crash or overheating and ensuring that the TIM in question was not likely to do so during normal or intensive use. The power cycle test method was achieved by fully utilizing its processing power, pushing the cooling and temperature as high as possible while using all the power available to the card.
[0058] To set up a power cycling program, the following functional software is not limited to one option, it is free and can be easily downloaded online. Stable and intensive graphics card / GPU stress test on Windows platform: FurMark, 3D Mark or Unigine Heaven GPU Monitor: MSI Afterburner, ASUS GPU Teak II Fan Controller: SpeedFan AUTOIT for running programs in a loop
[0059] Power cycling tests were performed by reaching a specific high temperature for 2.5 minutes while steadily cooling the GPU for another 2.5 minutes per cycle with a temperature interval of 35 to 85°C. After stress testing, the GPU card was disassembled to detect the degradation of the TIM morphology on both sides of the heat sink and chipset. Graph analysis software was further run to determine the total amount of defective area which can be converted to the pump-out degree of the TIM, and the number of cycles with 5% area pump-out was collected. An example of pump-out area calculation was as follows: 1)Get the pump out picture: 2) Using the software Labelme, label the die area (A1) and the total pump-out area (A2): Calculate pump out ratio = 100 x (A1-A2) / A1%.
[0060] <Synthesis Example 1> 25 g of ethylene and vinyl acetate copolymer (trade name: Nexxstar™ Low EVA-00111, commercially available from ExxonMobil, vinyl acetate content 7.5% by weight), and a 1,2-dichloro-1,3-diphenyl-2,4-tetramethylphenylacetate (1,2-diphenyl-2,4-tetramethylphenylacetate) having the following general formula: [ka] and 300 mL of xylene were added to a 1000 mL round bottom flask, stirred and heated to 130° C. to form a solution, then cooled to 80° C., 10 g of NaOH were added, the mixture was stirred at 80° C. for 3 hours, then 10 mL of methanol was added, further stirred at 80° C. for 2.5 hours, then 500 mL of ethanol was added to form a white solid powder. The white powder was filtered and washed with acetone, water, HCl (aqueous, pH 4) until pH 7, and acetone. The final product was dried under vacuum overnight and the structure was confirmed by FTIR as follows: the EVOH product has no acetate absorption but shows increased OH absorption. [ka]
[0061] <Synthesis Example 2> 20 g of polybutadiene represented by the following formula (trade name: NISSO-PB GI-3000 available from Nippon Soda Co., Ltd., Mn=3100, viscosity at 45°C=31.5 Pa·s, Tg=−37°C): [ka] was added to a 100 mL round bottom flask, and 0.01 g of dibutyltin dilaurate and 4.01 g of isocyanic acid octadecyl ester were added with stirring. The final mixture was stirred at 40°C for 5 hours to obtain the final product. It was confirmed by FTIR that the hydroxyl groups in the raw polybutadiene were consumed and urethane groups were identified in the final product.
[0062] [Examples 1 to 4 and Comparative Examples 1 to 4] The components listed below were used to prepare the thermal interface materials shown in Table 1.
[0063] The following components were used as component (A): Component (a-1): Polybutadiene represented by the following formula: [ka] (Product name: NISSO-PB GI-3000 available from Nippon Soda Co., Ltd., Mn = 3,100, viscosity at 45°C = 31.5 Pa·s, Tg = -37°C) Component (a-2): Polyethylene prepared in Synthesis Example 1.
[0064] The following components were used as comparisons for component (A): Component (a-3): Hydrogenated polybutadiene represented by the following formula: [ka] (Product name: NISSO-PB BI-3000 available from Nippon Soda Co., Ltd., Mn = 3,300, viscosity at 45°C = 18.0 Pa·s, Tg = -44°C) Component (a-4): Polybutadiene represented by the following formula: [ka] (Trade name: Krasol® LBH 5000M available from Cray Valley Co., Ltd., Mn=4500, viscosity at 25° C.=2.5 Pa·s, Tg=−45° C.) Component (a-5): Polybutadiene prepared in Synthesis Example 2.
[0065] The following components were used as component (B): Component (b-1): Zinc oxide filler having an average particle size of 0.2 μm (trade name: ZOCO 102 available from Zochem LLC) Component (b-2): Spherical aluminum filler having an average particle size of 2 μm (product name: TCP-02 available from TOYO ALUMINUM KK) Component (b-3): Spherical aluminum filler having an average particle size of 9 μm (trade name: TCP-09 available from TOYO ALUMINUM KK)
[0066] The following components were used as component (C): Component (c-1): Octadecane (melting point = approx. 28°C) Component (c-2): Hexatriacontane (melting point = 75-78°C) Component (c-3): 1-eicosanol (melting point = 64-66°C) Component (c-4): 1,2-tetradecanediol (melting point = approx. 67°C) Component (c-5): Paraffin wax (melting point = 52-54°C)
[0067] The following components were used as component (D): Component (d-1): n-decyltrimethoxysilane
[0068] The following components were used as component (E): Component (e-1): Hindered phenolic antioxidant (trade name: Irganox® 1010 available from BASF)
[0069] [Table 1]
[0070] [Table 2]
[0071] [Examples 5 to 7 and Comparative Examples 5 to 9] The thermal interface materials shown in Table 2 were prepared using the components above and below.
[0072] The following components were used as component (F): Component (f-1): Maleic anhydride-added liquid polybutadiene having a viscosity at 25°C of 6,500 MPa·s (trade name: Ricon® 130MA8 available from Cray Valley) Component (f-2): Bis(trimethoxysilylpropyl)amine
[0073] The following components were used as component (G): Component (g-1): Siloxane oligomer (trade name: DOWSIL OS-20 available from Dow Silicones Corporation)
[0074] [Table 3]
[0075] [Table 4]
[0076] According to the results in Tables 1 and 2, the comparative thermal interface materials (CE1, CE2, CE5, and CE6) had poorer pump-out resistance compared to the present thermal interface materials (IE1, IE3, and IE4), confirming that the hydroxyl groups in the polyolefin of component (A) are important in preventing pump-out. The treatment (capping) of the hydroxyl with isocyanic acid octadecyl ester also confirmed this finding, since the comparative thermal interface materials (CE3 and CE7) were poorer in preventing pump-out compared to the present thermal interface materials (IE1 and IE3). The comparative thermal interface material (CE4) showed poorer pump-out resistance and higher TI compared to the present thermal interface materials (IE1, IE2, and IE3), so the appropriate loading of the phase change material of component (B), especially the hydroxyl group-containing hydrocarbon wax, helps improve thermal conductivity and prevents pump-out.
[0077] However, the high loading of phase change material (which is the same as the phase change material) impairs the anti-pump-out performance, since 0.45 wt% phase change material (IE5) just meets the pass criteria, while 0.9 wt% phase change material (CE8) fails. The comparative thermal interface material (CE9) also requires a coupling agent, since it shows a much higher TI than the present thermal interface materials (IE1 and IE6) and cannot be used for TTV testing. Importantly, the introduction of the filler-polymer interaction promoter, component (F) interaction promoter, further improves the anti-pump-out performance of the present thermal interface material (IE6), and the introduction of component (G) solvent allows for a grease-like formulation instead of a pad (IE7).
[0078] [Comparative Examples 10 to 15] The thermal interface materials shown in Table 3 were prepared using the components above and below.
[0079] The following components were further used as component (A): Component (a-6): Polybutadiene represented by the following formula: [ka] (Product name: Krasol® H-LBH P 3000 available from Cray Valley Co., Ltd., Mn = 3,000, viscosity at 25°C = 1.5 Pa·s, Tg = -45°C)
[0080] The following components were further used as component (D): Component (d-2): Isopropyl tri(dioctyl pyrophosphate) titanate
[0081] The following components were used as component (H) for the crosslinker: Component (h-1): Methylated melamine-formaldehyde resin (product name: CYMEL (registered trademark) 325 resin available from CYTEC Industries Inc.)
[0082] The following components were used as component (I) for the catalyst: Component (i-1): Sulfonic acid (trade name: NACURE® 155 available from King Industries Inc.)
[0083] [Table 5]
[0084] [Table 6]
[0085] According to the results in Table 3, it was confirmed that other comparative thermal interface materials from the prior art (CE10-CE14) showed insufficient anti-pump-out performance. Also, excessive loading of the filler-polymer interaction promoter of component (F) would impair the TI performance (CE15). Therefore, the present thermal interface material showed more promise in TIM applications.
[0086] Industrial Applicability The thermal interface material of the present invention softens as its temperature increases in an electronic device during power cycling, but does not exhibit pump-out.The thermal interface material is therefore useful in thermal coupling materials for transferring heat from a heat-generating electronic component, such as a central processing unit (CPU) or a graphics processing unit (GPU), to a heat spreader, such as a heat sink.
Claims
1. 1. A thermal interface material comprising: (A) a polyolefin having at least two hydroxy groups per molecule; (B) at least one thermally conductive filler; (C) a phase change material having a melting point of 25 to 150° C.; (D) a coupling agent; Including, the content of component (B) is at least 80% by weight, the content of component (C) is 0.2-0.5% by weight, and the content of component (D) is 0.1-1% by weight, each based on the total weight of the thermal interface material; component (C) is octadecane, hexatriacontane, 1-eicosanol, 1,2-tetradecanediol, or a combination thereof; Component (A) has the following general formula: 【Chemistry 1】 wherein "m" is a positive number, with the proviso that "m" is a positive number that satisfies a number average molecular weight of 2,000 to 100,000 as measured by gel permeation chromatography.
2. Component (A) is a compound represented by the following general formula: 【Chemistry 2】 13. The thermal interface material of claim 1, further comprising a polybutadiene represented by the formula:
3. 10. The thermal interface material of claim 1, wherein component (B) is at least one thermally conductive filler selected from alumina, aluminum, zinc oxide, boron nitride, aluminum nitride, or aluminum oxide trihydrate.
4. 10. The thermal interface material of claim 1, wherein component (D) is at least one coupling agent selected from a silicon-based coupling agent, a titanium-based coupling agent, or an aluminum-based coupling agent.
5. Component (D) is represented by the following general formula: 【Chemistry 3】 In the formula, each R 4 are independently an alkyl group having 6 to 15 carbon atoms, and each R 5 are independently an alkyl group having 1 to 5 carbon atoms or an alkenyl group having 2 to 6 carbon atoms, and each R 6 are independently an alkyl group having 1 to 4 carbon atoms, "a" is an integer from 1 to 3, and "b" is an integer from 0 to 2, with the proviso that "a+b" is an integer from 1 to 3.
6. 10. The thermal interface material of claim 1, further comprising: (E) an antioxidant.
7. 10. The thermal interface material of claim 1, further comprising: (F) a filler-polymer interaction promoter.
8. 8. The thermal interface material of claim 7, wherein component (F) is at least one filler-polymer interaction promoter selected from liquid polybutadiene, silane-grafted polyolefin, or bis(trialkoxysilylalkyl)amine.
9. 10. The thermal interface material of claim 1, further comprising: (G) a solvent.
Citation Information
Patent Citations
Compliant and crosslinkable thermal interface material
JP2003509574A
Heat dissipation compound composition
JP2010278115A
Heat storage material composition and heat storage material
JP2014237775A
Thermal interface materials with ion scavengers
JP2017528538A
Synthetic resin, sealing resin, and resin material
JP2018070801A
